2010
DOI: 10.1111/j.1365-2788.2009.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

‘People who need people’: attachment and professional caregiving

Abstract: From the perspective of attachment theory, this paper discusses individual differences in the quality of caregiving by direct-care staff for persons with intellectual disabilities. Theoretical arguments and findings from related literature are cited to support the probable role of professionals' own attachment experiences and their mental representations thereof. Case examples are drawn from a study on video-based interaction guidance for direct-care staff in group homes for persons with multiple, serious disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 31 publications
1
81
0
1
Order By: Relevance
“…The importance of teacher-child relationships in general classes also applies to children with disabilities as a precondition for the children's quality of life and the reduction of problem behaviors (e.g., Hastings, 2005;Schuengel, Kef, Damen, & Worm, 2010), as reported by many previous studies (Blacher, Baker, & Eisenhower, 2009;Eisenhower, Baker, & Blacher, 2007;Lang, Marlow, Goodman, Meltzer, & Ford, 2013;Libbet, 2004;Mclntyre, Blacher, & Baker, 2006;Robertson et al, 2003;Roeden, Maaskant, Koomen, Candel, & Curfs, 2012). Eisenhower et al (2007) showed that the quality of teacher-child relationships was lower for 6-year-old children with intellectual disability compared with typically developing children.…”
Section: Teachers' Relationships With Disabled Childrenmentioning
confidence: 77%
See 1 more Smart Citation
“…The importance of teacher-child relationships in general classes also applies to children with disabilities as a precondition for the children's quality of life and the reduction of problem behaviors (e.g., Hastings, 2005;Schuengel, Kef, Damen, & Worm, 2010), as reported by many previous studies (Blacher, Baker, & Eisenhower, 2009;Eisenhower, Baker, & Blacher, 2007;Lang, Marlow, Goodman, Meltzer, & Ford, 2013;Libbet, 2004;Mclntyre, Blacher, & Baker, 2006;Robertson et al, 2003;Roeden, Maaskant, Koomen, Candel, & Curfs, 2012). Eisenhower et al (2007) showed that the quality of teacher-child relationships was lower for 6-year-old children with intellectual disability compared with typically developing children.…”
Section: Teachers' Relationships With Disabled Childrenmentioning
confidence: 77%
“…In contrast, children with autism spectrum disorder and intellectual disability generally show a different attachment-style tendency (Carvill, 2001;Clegg & Sheard, 2002;De Schipper, Stolk, & Schuengel, 2006;De Schipper & Schuengel, 2010;Schuengel, et al, 2010). Rogers, Ozonoff, & Maslin-Cole (1991) indicated that differences in attachment style compared with typically developing children were caused by their level of cognitive ability.…”
Section: Attachment Theory In Children With Developmental Disorders Amentioning
confidence: 98%
“…Such programs are especially important when persons with disabilities live in group homes, away from their parental attachment figures, have developed highly idiosyncratic, mostly nonverbal means to express their emotional needs, or display aversive behaviors that interfere with positive, harmonious interaction (Janssen, Riksen-Walraven, & Van Dijk, 2003b;Janssen, Schuengel, & Stolk, 2002;Schuengel et al, 2010). Most programs train staff in general skills for interacting with persons with intellectual or multiple disabilities (e.g., Maes, Lambrechts, Hostyn, & Petry, 2007).…”
Section: Representational Processes and Intervention Effectivenessmentioning
confidence: 98%
“…One study on children with autism spectrum disorders showed that parental autonomous attachment representations were associated with higher quality functional emotional interaction (Seskin, Feliciano, Tippy, Yedloutschnig, Sossin, & Yasik, 2010). No studies have been reported on the relevance of attachment representations for providing daily care to children and adults with disabilities in a professional context, but the evidence regarding the importance of representational processes in parents of children with disabilities, as well as the evidence regarding the relevance of attachment representations of therapists and group caregivers, make it plausible that attachment representations play a role in professional caregiving for persons with disabilities as well (Schuengel, Kef, Damen, & Worm, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Alignment and involvement are seen as the core of the care giving in caring for persons with an intellectual disability [19]. Sensitivity and attentiveness are necessary to properly interpret signals [20].…”
Section: Discussionmentioning
confidence: 99%